Corporate Restructuring of Industrial and Commercial Bank of China (ICBC), Motivators and Impacts - Xu, Xinliang (2006)
In recent years, corporate restructuring has become a common practice undertaken by firms for surviving an increasingly fierce business environment. In the present work, a case study is employed to explore the motivators and impacts of restructuring of China's largest bank, Industrial and Commercial Bank of China (ICBC). This paper begins by illustrating the theoretical explanations and implications regarding corporate restructuring. Taking into account the Chinese institutional context, the theoretical framework implies that the framework regarding motivators and impacts of restructuring could be applicable to state-owned enterprises (SOEs), which ICBC used to be. Then, it presents a case study of ICBC concerning the inside story of its restructuring. It is demonstrated that the motivators of ICBC's restructuring lie in the changes in the business environment, ICBC's weak governance, poor strategic control, and poor performance; whilst the impacts are on ICBC's corporate governance, organizational structure and strategic control, performance, and employee (other impacts). It also includes some comparisons between the relevant literature and the findings from the case study. Hopefully, this study could contribute to the literature on the topic of restructuring of SOEs (state-owned commercial banks in particular).